COST-EFFECTIVENESS ANALYSIS OF STUNTING INTERVENTION THROUGH WHATSAPP APPLICATION FOR RURAL COMMUNITY EDUCATION (CASE STUDY IN BALONGCABE VILLAGE, BOJONEGORO DISTRICT) - Putri, Nuzulul Kusuma; Azzahra, Lama'ah (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Bojonegoro Regency is one of the regencies with a high prevalence of stunting at 23.9%, which is higher than the provincial prevalence of 23.5% and 21.1% nationally. Kedungadem District occupies the second highest stunting case, as many as 258 toddlers and 14 of them are in Balongcabe Village. The purpose of this study was to analyze the cost-effectiveness of stunting intervention through a public education program called Hotline Stunting that utilizes the automatic message feature on the WhatsApp Business application for the people of Balongcabe Village, Bojonegoro Regency. This research method was true-experimental by providing a stunting intervention program and the research subjects were Balongcabe village cadres. During the program's trial period in August 2021, there were 144 children under five in Balongcabe Village. The cost analysis method used Cost Effectiveness Analysis (CEA) by calculating the ratio of the total costs incurred to implement the program with program cost effectiveness that produced the same outcome, namely stunting prevention. Based on the results of the CEA calculation, the use of the Hotline Stunting program in Balongcabe Village was 4,314 rupiah and the USE Questionnaire calculation was 85.43%, indicating that the Hotline Stunting Program that utilizes the WhatsApp Business Application with a low amount will be effectively run as one stunting prevention program and categorized into a program that is very feasible and easy to use, so it can be recommended to continue to be developed in Balongcabe Village.